anonymous
  • anonymous
I award medals to whoever helps me!!! given f(x)=3x-1 over 2. Solve for f^-1 (4)
Algebra
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
1 3 5 7
anonymous
  • anonymous
wow this is tough
anonymous
  • anonymous
lol tell me about it! I have been working on this single problem for 30 minutes trying to figure out how to solve it

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
and I have had 0 progress with it :p
anonymous
  • anonymous
lol
anonymous
  • anonymous
i've got nothing sry man
anonymous
  • anonymous
it's okay :-) Thanks for trying!
anonymous
  • anonymous
I gave you a medal because you tried to help me :-) Nobody else has and I posted this on another thing too
anonymous
  • anonymous
nah dude keep the medal i don't deserve it
phi
  • phi
f−1(x) means the inverse of f(x) it is asking for the x that makes f(x)= 4 we can find f−1(x) (though this is not necessary) start with y = (3x-1)/2 swap x and y x = (3y -1)/2 solve for y 2x = 3y -1 2x + 1 = 3y y = (2x+1)/3 now plug in 4 for x to get y = (2*4+1)/3 = 9/3 = 3
phi
  • phi
another way is to solve for x in f(x)=4 4 = (3x-1)/2 multiply both sides by 2 8 = 3x -1 add 1 to both sides 9 = 3x divide both sides by 3 3 = x
anonymous
  • anonymous
Oh wow!! That clears everything up so much! Thank you SO much!!
anonymous
  • anonymous
f(x)=4 4 = (3x-1)/2 X both sides 2 8 = 3x -1 +1 to both sides 9 = 3x / 3 x=3 , Hope it helped! Could use a medal if it did!
anonymous
  • anonymous
Thanks Hannah! It did help but I already gave the medal to phi. You both helped me a lot! If it helps, I became your fan and your smart score was boosted from 19 to 24.

Looking for something else?

Not the answer you are looking for? Search for more explanations.